2010
DOI: 10.1017/s1138741600004005
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory Factorial Analysis of the Brazilian Version of the Competitive State Anxiety Inventory-2 (CSAI-2)

Abstract: 453The aim of this study was to assess the factorial structure of the Brazilian version of CSAI-2, using several structures suggested in previous studies. Two samples consisted of Brazilian soccer players, 266 from regional level (age 22.87 ± 4.08 years; athletic experience 11.32 ± 4.15 years) and 263 from national level (age 23.16 ± 4.37 years; athletic experience 11.11 ± 4.78 years) were used. The CSAI-2 is a 27-item inventory that measures negativism, physiological activation and self-confidence in a compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
0
9
0
2
Order By: Relevance
“…These recommendations were based on theoretically and empirically guided modifications that aimed to maintain the 3-factor theoretical structure of the original instrument (Cox et al, 2003). Previous research has demonstrated the superior fit of the CSAI-2R model (17 items) across several different cultures and languages (Coelho et al, 2010;Fernandes et al, 2012;Fernández, Rio, & Fernandez, 2007;Lundqvist & Hassmén, 2005;Raudsepp & Kais, 2008) although only the intensity dimension was examined in these studies. The only known study that tested this model across all three response dimensions (Martinent et al, 2010) provided support for the reliability and validity of this reduced model but the elimination of the first somatic anxiety item was suggested.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These recommendations were based on theoretically and empirically guided modifications that aimed to maintain the 3-factor theoretical structure of the original instrument (Cox et al, 2003). Previous research has demonstrated the superior fit of the CSAI-2R model (17 items) across several different cultures and languages (Coelho et al, 2010;Fernandes et al, 2012;Fernández, Rio, & Fernandez, 2007;Lundqvist & Hassmén, 2005;Raudsepp & Kais, 2008) although only the intensity dimension was examined in these studies. The only known study that tested this model across all three response dimensions (Martinent et al, 2010) provided support for the reliability and validity of this reduced model but the elimination of the first somatic anxiety item was suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Athletes completed a Brazilian-Portuguese version (Coelho, Vasconcelos-Raposo, & Mahl, 2010) of the original CSAI-2 (Martens et al, 1990) that included the direction and Downloaded by [Chinese University of Hong Kong] at 05:01 26 December 2014 the frequency response dimensions. This instrument consists of 27 items measuring three dimensions: cognitive anxiety (Items 1, 4, 7, 10, 13, 16, 19, 22, and 25), somatic anxiety ( Items 2,5,8,11,14,17,20,23,and 26) and self-confidence ( Items 3,6,9,12,15,18,21,24,and 27).…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess pre-competitive anxiety, we used the Competitive State Anxiety Inventory (CSAI-2), originally developed by Martens et al (1990b) and validated for the Brazilian context by Coelho, Vasconcelos-Raposo & Mahl (2010). This instrument is composed of 27 items distributed in three subscales: CA (α = 0.85); SA (α = 0.88); and SC (α = 0.90).…”
Section: Instrumentsmentioning
confidence: 99%
“…Results suggest preliminary CSAI-2 adequacy evidence for Brazilian athletes. However, results suggest some changes may be necessary so the instrument may present acceptable psychometric properties (Bartholomeu, Montiel, & Machado, 2013;Coelho, Vasconcelos-Raposo, & Mahl, 2010). Coimbra (2011) transculturally adapted the Athletic Coping Skills Inventory-28 (Smith et al, 1995) for Brazilian athletes.…”
Section: Introductionmentioning
confidence: 99%